The Effect of Ethanol Extract of Bangunbangun Leaf (Plectranthus amboinicus (Lour) Spreng) as Preventive and Curative to Toxic Effect of Rhodamin B in a Intestine Histology of White Rat (Rattus norvegicus) - Rina Mariska Haloho; Melva Silitonga (JBIO: jurnal biosains (the journal of biosciences), 2015)
This study aims to know the effect of ethanol extract of bangunbangun leaf (Plectranthus amboinicus (Lour) Spreng) to were body weight, ratio of intestine to body weight, and intestine histology of the white rat (Rattus norvegicus). This study is experimental with non factorial completely randomized design. This research used 40 rats which devided into 8 groups, they are control (CMC 1%), rhodamin B, ethanol extract of bangunbangun leaf with graded doses 350 mg/kg bw, 700 mg/kg bw dan 1050 mg/kg bw. In preventive treatment, EEDB was given on 1 day to 42 day, rhodamin B was given on the 22 day to 42. In curative treatment, rhodamin B was given on the 1 day to 21 day then continued by giving EEDB from the 22 day until 42 day. Histology overview was done with hematoxilin eosin staining. The data obtained were analyzed by ANOVA and continued by LSD using SPSS versi 16. The result showed that preventive treatment increased body weight at dose 350 mg/kg bw. EEDB lowered ratio of intestine weight to body weight dose 700 mg/kg bw and lowered thickness of intestinal mucosa at dose 350 mg/kg bw. In curative treatment increased body weight at dose 700 mg/kg bw, lowered ratio of intestine weight to body weight at dose 350 mg/kg bw and lowered thickness of intestinal mucosa at dose 1050 mg/kg bw. Key Word: Bangunbangun (Plectranthus amboinicus (Lour) Spreng), rhodamin B, preventive, curative.